ASESMEN PEMBELAJARAN IPA PADA KURIKULUM MERDEKA: IMPLEMENTASI, EFEKTIVITAS, DAN ARAH PENGEMBANGANNYA - Suryana, Andri; Yuliati, Yuyun; Barnar Komaruddyi, Yudi; Rohayati, Dede; Wulan Trisnawati, Inne; Kurniawati, Iis; Mardiana, Sitti; Sri Rahayu, Novi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Merdeka Curriculum has transformed the assessment paradigm from merely measuring learning outcomes into an integral part of the learning process. In science learning, assessment serves to identify students’ prior knowledge, monitor learning progress, provide feedback, and comprehensively measure the achievement of competencies. This study aims to analyze the implementation of science learning assessment in the era of the Merdeka Curriculum based on published research findings. The study employed a literature review method by analyzing 21 national and international scientific articles published between 2022 and 2026. Data were analyzed through the stages of identification, selection, classification, and synthesis of research findings. The results indicate that science learning assessment is predominantly characterized by diagnostic, formative, summative, authentic, and digital assessments. These assessment practices have been shown to support differentiated learning, enhance critical thinking skills, scientific literacy, learning motivation, and student engagement in the learning process. However, several challenges remain, particularly regarding teachers’ competence in developing assessment instruments, limited utilization of technology, and the suboptimal use of assessment results for instructional improvement. Therefore, strengthening teachers’ competencies, developing Higher-Order Thinking Skills (HOTS)-based assessment instruments, and integrating digital technology into assessment systems are essential to support the successful implementation of the Merdeka Curriculum.